Sailor Diplomat : Nomura Kichisaburō and the Japanese-American War - Mauch, Peter (Peter Cameron) (Book collections on Project MUSE., 2011)
As Japan's pre-Pearl Harbor ambassador to the United States, Admiral Nomura Kichisaburo (1877-1964) played a significant role in a tense and turbulent period in Japanese-US relations. This biography casts light on the life and career of this important figure.